Evaluation of Indonesian Education Loan Programs: An Overview of Challenges and Implications in Public Access - Hidayat, Rahmad; Hidayat, Ara; Jaenudin, Mohamad (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2023)
The growing demand for education and the increasing awareness of its value have also had an impact on the financing of higher education. Governments are working to meet the growing demand for sustainable higher education with better quality but with limited resources. Although many governments have launched student loan programs, the debate about the failure of student loan programs in developing countries is still unresolved. This study aims to collect and analyze articles related to the reasons why student loan programs are not more widely recognized in Indonesia by analyzing the implications of student loans. The method used in this study is a literature review by collecting various sources of articles related to the issues discussed. The results of the study show that there are many problems with student loans that are not widely known, such as irrelevant student loan policies, challenges in their application systems, and unrecoverable loans that eventually burden the community. The role of government, bank trust, and community commitment are the factors that determine the level of success in achieving these student loans